Day for night [videorecording (DVD)] - Truffaut, François; Truffaut, François; Truffaut, François; Bisset, Jacqueline, 1944-; Bisset, Jacqueline, 1944-; Cortese, Valentina (The Criterion collection, 2015)
The leading lady is recovering from a nervous breakdown, another performer is soused on the set, unions threaten to walk, shooting must finish before the insurance lapses and a cat can't hit its mark. Is this any way to make a film?